PENGARUH KOMUNIKASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA BANK SYARIAH INDONESIA DI KUTACANE KABUPATEN ACEH TENGGARA - Joko Gafar; Rila Maufira; Ardi Hirmansah (EKSPOLHUM, 2026)
Employee performance varies from one employee to another, as employee performance is individual. Performance refers to employee work achievements measured against standards or criteria established by the company. The purpose of this study was to determine and analyze the influence of communication and motivation on employee performance at Bank Syariah Indonesia in Kutacane. This study used a quantitative approach, a research method based on the philosophy of positivism, to examine a specific population or sample. The data source was obtained from employees at Bank Syariah Indonesia in Kutacane by distributing questionnaires, and respondents' responses were measured using a Likert scale. Secondary data, sourced from the company, included sales data, a general overview of the company, and its organizational structure. The collected data was analyzed using SPSS software, consisting of descriptive statistical tests, classical assumption tests, multiple linear regression, simultaneous and partial hypothesis tests, and coefficients of determination. The results of the study indicate that communication and motivation simultaneously have a positive and significant effect on employee performance at Bank Syariah Indonesia in Kutacane. Partially, communication has a positive and significant effect on employee performance. Partially, motivation has a positive and significant effect on employee performance at Bank Syariah Indonesia in Kutacane. The coefficient of determination (R2) of communication, motivation, and work environment explains 57.9% of employee performance at Bank Syariah Indonesia in Kutacane, while the remaining 42.1% is explained by independent variables not examined